Peran Kantor Pertanahan Dalam Memberikan Jaminan Kepastian Hukum Hak Atas Tanah Melalui Program Pendaftaran Tanah Sistematis Lengkap (PTSL) Di Kota Semarang - Mastur, Mastur; Arsita Dewi, Ery (Fakultas Hukum Universitas Wahid Hasyim, 2024)
AbstractThis research discusses the role of the Land Office in providing legal certainty for land rights through the Comprehensive Systematic Land Registration Program (PTSL) in the city of Semarang. The Constitution of the Republic of Indonesia of 1945 establishes the foundation that land, water, and natural resources are controlled by the state for the prosperity of the people. The Basic Agrarian Law (UUPA) serves as the legal framework governing land tenure and assigns the government the task of land registration. Land registration is an effort to provide legal certainty for land rights. The PTSL program is implemented as part of the government's efforts to expedite land registration in an easily understandable and cost-effective manner. However, there are challenges in its implementation, such as the lack of data validity due to prioritizing speed over accuracy. The Land Office, as the land registration authority in Indonesia, plays a key role in the implementation of PTSL. This research focuses on the implementation of PTSL in the city of Semarang, acknowledged as the best in Indonesia. The aim is to evaluate the extent of the Land Office's role in providing legal certainty for land rights through this program and to identify potential challenges. By considering the experience of land certification that prioritizes speed, this research is expected to provide insights into the effectiveness and challenges of PTSL implementation at the local level, as well as the Land Office's contribution to ensuring legal certainty for land rights in the city of Semarang.